Living shrines of Uyghur China - Citron, Beth; Dawut, Rahil; Papas, Alexandre (The Monacelli Press, 2013)
Lisa Ross's ethereal photographs of Islamic holy sites were created over the course of a decade on journeys to China's Xinjiang region in Central Asia, historically a cultural crossroads but an area to which artists and researchers have generally been denied access since its annexation in 1949. These monumental images show shrines created during pilgrimages, many of which have been maintained continuously over several centuries; visitation to the tombs of saints is a central aspect of daily life in Uyghur Islam, and its pilgrims ask for intercession for physical, mental, and spiritual ailments. The shrines, adorned with small devotional offerings that mark a prayer or visit, are poignant representations of collective memory and a pacifistic faith, and endure despite vulnerability to natural forces of sand, heat, and powerful winds. Their simplicity and austerity as captured by Ross invoke ideas of spirituality, eternity, and transcendence. Three essays--by a historian of Central Asian Islam, a Uyghur folklorist, and the curator of an accompanying exhibition at the Rubin Museum of Art--situate the photographic content in context. This volume emerges at a critical time, as modernization and new policies for development of China's far west bring about rapid, extreme, and irrevocable change; the region is its largest source of untapped natural gas, oil, and minerals. Many of the sites in Ross's work are threatened by political and economic pressures--her images are valuable, therefore, not only for their intrinsic beauty, but as an important record of a rich and vibrant culture